Pengaruh Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Bintang Selatan Agung Palembang - Aras Tulip; Imam Suroso; Indah Mawarni; Vivin Afini (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2018)
This study aims to determine the level of the relationship between work discipline on employee performance. The population in this study were 120 people and the sample was 92 people. The analysis technique is done by qualitative analysis and quantitative analysis. The results of this study can be concluded that the relationship between work discipline and employee performance using the product moment correlation analysis tool obtained rxy correlation value of 0.997. When consulted with r table 0.997 it is at 0.80-1,000 which means that the relationship between work discipline and performance is very strong. The influence of work discipline and employee performance using the determination coefficient determination formula obtained a value of 99.4%, meaning that work discipline has an effect of 99.4% on performance. While 0.6% is influenced by other factors not examined. The magnitude of the qualitative analysis of work discipline and employee performance in table 8-16 concerning work discipline questions in table 17-27 about thequestion of employee performance, it is concluded that the work discipline carried out by employees is still not good. Thus it can be concluded that work discipline has a role in improving employee performance.